Training Doctoral Supervisors in Artistic Research (EAAE Annual Conference Proceedings, 2023)
The abstract discusses the development of a video-based scenariodriven online PhD supervisor training for the field of artistic research. The resource is developed as part of a transdisciplinary European Erasmus+ project that tackles artistic research within a broad range of disciplines, from performative and visual art to design and architecture. The architectural and artistic research fields are still young and unevenly developed. They include a wide range of approaches, from practicebased research exploring established peer-recognised creative practices to topic-based research projects, where recent graduates aim to build their careers by developing knowledge aimed at academia or artistic practice.